Targeting TRPV1 channels in desensitized neural afferent pathways may help mitigate pain and lower urinary tract symptoms caused by prostatitis - Jiang, ZhiPeng; Li, AnGuo; Luo, Wen; Luo, XiKe; Liang, DeCan; Li, Jing; Tang, KaiHua; Liu, Lei; Long, ZongMin; Miao, Ruiyu; Jian, Lei; Gong, XiaoChuan; et al. (Frontiers in Pharmacology, 2025)
Chronic prostatitis/chronic pelvic pain syndrome (CPPS/CP) is a prevalent urinary disorder primarily characterized by pelvic pain and discomfort, bladder dysfunction, and sexual dysfunction. Currently, there is no effective method to alleviate the pain and lower urinary tract symptoms associated with chronic prostatitis. Resiniferatoxin (RTX), a highly potent TRPV1 receptor agonist, functions as a molecular analgesic by desensitizing TRPV1-expressing nerves. While RTX has demonstrated significant efficacy in treating various conditions, research on its application for prostatitis remains lacking. Consequently, we established a prostatitis model to investigate whether RTX could alleviate the symptoms associated with this condition. Our observations indicated that both low-dose (200 μg/kg) and high-dose (300 μg/kg) RTX effectively relieved pain and lower urinary tract symptoms caused by prostatitis. We noted that RTX reduced the expression of central pain-inducing substance P by reducing TRPV1 expression in the dorsal root ganglia (DRG), thereby mitigating pain. RTX also desensitizes bladder nerves by reducing TRPV1 expression in the bladder, which helps alleviate lower urinary tract symptoms caused by prostatitis. Collectively, these findings suggest that RTX may serve as a viable treatment option for alleviating prostatitis-induced pain and lower urinary tract symptoms through neural desensitization, presenting a promising therapeutic avenue for patients with prostatitis.